Correspondence between white matter hyperintensities and regional grey matter volumes in Alzheimer's disease - Yi, Fangyuan; Wang, Jirui; Lin, Meiqing; Li, Baizhu; Han, Shiyu; Wang, Shan; Jin, Yingbin; Hu, Ning; Chen, Yutong; Shang, Xiuli (Frontiers in Aging Neuroscience, 2024)
Objective: White matter hyperintensities (WMH) are the most common neuroimaging manifestation of cerebral small vessel disease, and is frequently observed in Alzheimer's disease (AD). This study aimed to investigate the relationship between WMH and cognition and to verify the mediation of grey matter atrophy in this relationship. Methods: The diffusion tensor imaging (DTI) technique analyses white matter fibre tract to assess white matter integrity. Voxel-based morphometry was applied to measure the grey matter volume (GMV). A linear regression model was applied to examine the associations between WMH and GMV, and mediation analyses was performed to determine the mediating role of regional GMV in the effect of WMH on cognitive function. Results: Compared to the HC group, AD group have 8 fibre tract fractional anisotropy (FA) decreased and 16 fibre tract mean diffusivity (MD) increased. Compared to AD without WMH, AD with high WMH had 9 fibre tracts FA decreased and 13 fibre tracts MD increased.. High WMH volume was negatively correlated with GMV in the frontal-parietal region. Low WMH volume was also negatively correlated with GMV except for the three regions (right angular gyrus, right superior frontal gyrus and right middle/inferior parietal gyrus), where GMV was positively correlated. Mediation analysis showed that the association between WMH and excutive function or episodic memory were mediated by GMV in the frontal-parietal region. Conclusion: Damage to white matter integrity was more severe in AD with WMH. Differential changes in DTI metrics may be caused by progressive myelin and axonal damage. There was a negative correlation between WMH and grey matter atrophy in frontal-parietal regions in a volume-dependent manner. This study indicates the correspondence between WMH volume and GMV in cognition, and GMV being a key modulator between WMH and cognition in AD. This result will contribute to understanding the progression of the disease process and applying targeted therapeutic intervention in the earlier stage to delay neurodegenerative changes in frontal-parietal regions to achieve better treatment outcomes and affordability.